Perspective Taking Through Film: Educating Pre-Service and In-Service Teachers About Autism - Kelleher, Jacqueline P. (Journal of the American Academy of Special Education Professionals, 2015)
When it comes to educating students with autism in the classroom, teachers’ perceptions and attitudes toward inclusion are essential. Professional development that enhances perspective taking about autism is powerful if it leads to depth of understanding and action. Instructional media can play a role in raising viewer awareness; unfortunately, there are significant difficulties locating appropriate media concerning autism spectrum disorders (ASD) for developing teacher perspective taking skills. A film was developed for this project that shows a first person perspective of a student with autism in a classroom. Findings from 500 teacher participants on a post-test instrument regarding the film’s content show increased perspective taking regarding ASD deficits after the film. Results showed that through this approach, teachers were able to deepen their understanding about the deficit areas. Post-test results and feedback from reflective, post-film discussion show teacher understanding of deficits that may be present in those with ASD.